Characteristics and Permeability Properties of Sago Starch Edible Film - Payung Layuk; Joula Sondakh; Marietje Pesireron (AGRITEKNO: Jurnal Teknologi Pertanian, 2019)
The research was aimed to study the potential of sago starch as an edible film or edible wrapper, which is used as a barrier to mass transfer. The edible film was made from sago starch with the addition of nutmeg pectin at concentrations of 0%, 10%, 15%, 20% and 25% by adding glycerol as much as 20% w/w. The results showed that the addition of nutmeg pectin and glycerol was able both to improve film characteristics and to control mass transfer. Addition of nutmeg pectin caused an increase in the Water Vapor Permeability (WVP) value of the film. Edible sago starch films can be used as a dodol packaging material because it protects products from oxidation and fungi, and is a better barrier from oxygen when compared to synthetic films. The increase in nutmeg pectin concentration caused an increase in WVP and exponential oxygen permeability. Keywords: edible film, sago, wrapping